1994
DOI: 10.1210/en.134.1.337
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic degradation of insulin-like growth factor (IGF)-binding protein-3 by porcine ovarian granulosa cells in culture: regulation by IGF-I

Abstract: Porcine ovarian granulosa cells in culture secrete glycosylated insulin-like growth factor (IGF)-binding protein-3 (IGFBP-3), which inhibits gonadotropin and IGF action in the ovary. Synthesis of IGFBP-3 is stimulated by IGF-I and attenuated by gonadotropin. The purpose of the present study was to determine whether IGFBP-3 levels were also regulated via proteolysis. Exogenously added nonglycosylated recombinant human IGFBP-3 (rhIGFBP-3) was significantly degraded over time by a soluble serine-specific protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 0 publications
1
24
1
Order By: Relevance
“…Recently it was reported that IGFBPs are cleaved by specific proteases [12,13]. Once IGFBPs are cleaved by proteases, their binding affinity for IGF decreases [14], resulting in a change in its effect on IGF [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that IGFBPs are cleaved by specific proteases [12,13]. Once IGFBPs are cleaved by proteases, their binding affinity for IGF decreases [14], resulting in a change in its effect on IGF [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This IGFBP-3 protease activity disappears rapidly after parturition and is thought to arise from the placenta (5,8). IGFBP-3 protease activity has also been identified in a variety of other situations such as in conditioned medium from MCF-7 breast cancer cells (9), skin blister fluid (10), and in ovarian follicular fluid (11). The relationship between each of these protease activities is not clear at this point in time.…”
mentioning
confidence: 99%
“…IGF-I has been shown to inhibit the plasmin-induced and plasmin-like protease-induced IGFBP-3 proteolysis in human osteosarcoma cells and porcine ovarian granulosa cells, respectively (13,14). In the former, the inhibition was believed to be mediated by depressing the activity of uPA (13).…”
Section: Resultsmentioning
confidence: 99%